THE METHODOLOGICAL TRAINING OF FUTURE UNIVERSITY TEACHERS TO IMPLEMENT INTERCULTURAL FOREIGN LANGUAGE EDUCATION: THE COMPETENCY-BASED APPROACH - Maiier, Nataliia (Advanced Education, 2017)
The article highlights peculiarities of future teacher methodological training in order to realise intercultural foreign-language education through the competency-based approach. The competency-based approach is a methodological basis of the contemporary higher education system. That is why it is important to substantiate main features of the methodological teacher training for implementing intercultural foreign language education based on this approach. The research aim was obtained with the help of scientific methods: the comparison and system analysis of psychological, pedagogical, methodological sources, generalisation and conceptualisation, positive experience generalisation of future university teachers methodological training in order to implement intercultural foreign-language education, education process monitoring, pilot training that highlights the effectiveness of creative academic and professionally methodological tasks. The future university foreign language teachers’ methodological training to implement intercultural education is viewed in the light of their methodological competency formed as a result of professional training at tertiary institutions, which is manifested in the ability to effectively fulfill all kinds of professional and methodological activities, as well as long-term readiness for professional, methodological, and personal self-development and self-improvement for the lifelong period. In the context of the competency-based approach, formation and development of future foreign language teachers’ methodological competency are provided by mastering its structural components – competencies and sub-competencies. In the process of students’ methodological training to implement intercultural foreign language education, their mastering of sub-competence within lingvosociocultural competence is of great importance. A future university foreign language teacher’s sub-competence as a part of lingvosociocultural competence is a complex and dynamic interplay of specific methodological knowledge and skills that enable to organise students’ intercultural education. The future university teachers’ methodological training to implement intercultural foreign language education takes place in different forms of educational process organisation. Master’s students majoring in foreign language teacher education acquire methodological knowledge and skills within the normative discipline “Methods of teaching foreign languages at higher educational institutions”, the elective discipline “Methods of using educational materials for the formation of foreign language communicative competence”, and during student teaching period. Substantiation of the criteria, methods and assessment tools of future university foreign language teachers’ methodological training to implement intercultural education is the prospect of further research studies.